Astaxanthin ameliorates inflammation, oxidative stress, and reproductive outcomes in endometriosis patients undergoing assisted reproduction: A randomized, triple-blind placebo-controlled clinical trial - Rostami, Sahar; Alyasin, Ashraf; Saedi, Mojtaba; Nekoonam, Saeid; Khodarahmian, Mahshad; Moeini, Ashraf; Amidi, Fardin (Frontiers in Endocrinology, 2023)
Purpose In a randomized, triple-blind, placebo-controlled clinical trial (RCT) including 50 infertile women with endometriosis candidate for assisted reproductive techniques (ART), we studied the effect of Astaxanthin (AST) on pro-inflammatory cytokines, oxidative stress (OS) markers, and early pregnancy outcomes. Methods Before and after 12 weeks of AST treatment (6 mg per day), blood serum and follicular fluid (FF) samples were collected from 50 infertile women with endometriosis stage III/IV undergoing ART. Pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) and OS markers (malondialdehyde [MDA], superoxide dismutase [SOD], catalase [CAT], and total antioxidant capacity [TAC]) were measured in the serum and FF. ART outcomes were also compared between the groups. Results Increased serum levels of TAC (398.661 ± 57.686 vs. 364.746 ± 51.569; P = 0.004) and SOD (13.458 ± 7.276 vs. 9.040 ± 5.155; P = 0.010) were observed after AST therapy in the treatment group. Furthermore, serum MDA (14.619 ± 2.505 vs. 15.939 ± 1.512; P = 0.031) decreased significantly following antioxidant treatment. In addition, significantly lower serum levels of IL-1β (4.515 ± 0.907 vs. 6.8760 ± 0.8478; P = 0.000), IL-6 (5.516 ± 0.646 vs. 5.0543 ± 0.709; P = 0.024) and TNF-α (2.520 ± 0.525 vs. 2.968 ± 0.548; P = 0.038) were observed after AST treatment. In addition, AST supplementation led to an improved number of oocytes retrieved (14.60 ± 7.79 vs. 9.84 ± 6.44; P = 0.043), number of mature (MII) oocytes (10.48 ± 6.665 vs. 6.72 ± 4.3; P = 0.041), and high-quality embryos (4.52 ± 2.41 vs. 2.72 ± 2.40; P = 0.024). Conclusion AST pretreatment can modulate inflammation and OS in endometriosis-induced infertile patients. ART outcomes also improved after 12 weeks of AST therapy. Our results suggest that AST can be a potential therapeutic target for infertile patients with endometriosis undergoing ART.